Comparison of the National Curriculum from the STEM Perspective with Focus on Technologies and Engineering in the Czech Republic, Poland and Slovakia - Dostal, Jiří (TEM Journal, 2023)
The curriculum naturally changes as the world changes. The shape of education responds to social need changes, rapid technological developments, and changes in nature, especially in the context of global warming. On the other hand, cultural frameworks and practices, which make national curricula specific, have a stabilizing function. In the Czech Republic, work is currently underway to innovate a key national curriculum document that specifies what, to what extent, and under what conditions pupils learn in primary schools. To reflect on the new competencies, the new curriculum, and its organization based on different views and experiences from abroad, this comparative study was carried out to compare the curricula in the Czech Republic, Slovakia, and Poland. We did not focus on STEM education as a whole, but only on the field of technology and engineering. Thus, we obtained an answer to the question of whether engineering education is implemented in primary schools in these countries. The aim was not only to compare content but to bring a deeper understanding of the subject matter. To this end, we established 6 criteria based on which we made the comparison. Finally, based on the results of the analysis, we discussed the barriers to the implementation of STEM concepts in education in the Czech Republic and drew negative consequences that could be manifested in the case of ill-considered interventions in the national curriculum.